Associations between screen time and cognitive development in preschoolers. Issue 2 (26th August 2021) - Zhang, Zhiguang; Adamo, Kristi B; Ogden, Nancy; Goldfield, Gary S; Okely, Anthony D; Kuzik, Nicholas; Crozier, Mitchell; Hunter, Stephen; Predy, Madison; Carson, Valerie
Abstract: Objectives: To examine the cross-sectional associations between screen time and cognitive development in preschoolers. Methods: Participants were 97 preschoolers (36 to 60 months) in Alberta and Ontario, Canada in the supporting Healthy physical AcTive Childcare setting (HATCH) study. The time that children spent watching television, videos or DVDs (television time) or playing video or computer games (video game time) on a television, computer, or portable device was assessed using a parental questionnaire. Television time and video game time were summed to calculate total screen time. Adherence to the screen time recommendation (≤1 hour/day) of the Canadian 24-Hour Movement Guidelines was calculated. Expressive vocabulary and working memory were assessed using the Early Years Toolbox. Due to the distribution of working memory, it was categorized as a binary variable based on the median score. The associations between screen time and cognitive development were examined using mixed models (expressive vocabulary) or generalized mixed models (working memory). Results: Screen time was not associated with expressive vocabulary. Preschoolers who had higher total screen time were less likely to have better working memory (OR=0.52; 95%CI:0.31, 0.88), despite the null associations for television time (P=0.155) and video game time (P=0.079). Preschoolers who met the screen time recommendation were more likely to have higher working memory capacity (OR=3.48; 95%CI:1.06, 11.47), compared to those who did not meet the recommendation. Conclusion: Limiting total screen time to no more than one hour per day may facilitate working memory development in preschoolers. Screen time may be unrelated to expressive language development in this age group.